ANALISIS PENGARUH KUALITAS LAYANAN DAN TARIF TERHADAP KEPUASAN KONSUMEN DAN DAMPAKNYA PADA LOYALITAS DAN KOMITMEN RELASIONAL (Studi pada Rumah Sakit Bhayangkara Semarang) - 10.42.02.0016, Agus Dhermawan (Jurnal Mahasiswa Pasca Sarjana, 2013)
Hospital has a social function. Beside That, hospital has economic function aimed at obtaining profits. With the increasing number of existing hospitals and increasing the range of services provided by various hospitals, it made increasingly add to the competition in the healthcare business also. RS Bhayangkara Semarang which incidentally is type B hospital which was established to serve the interests of the health of police officers in particular and society in general are required to serve consumers ( patients ) as well as possible. With this study writer expect RS Bhayangkara Semarang can improve their services and to compete with other hospitals in an effort to serve the needs of society in terms of health . This study aims to analyze quality of service and rates provided by RS Bahyangkara Semarang as independent variables on satisfaction , loyalty and commitment relational RS Bhayangkara Semarang as the dependent variable. Sampling technique taken with accidental sampling , with the population is a member of the Police. Observed samples taken while the patient is ambulatory and inpatient . While the number of samples taken amounted to 119 pieces . From the data analysis it can be concluded ( 1 ) the quality of services and rates have a positive effect on patient satisfaction ( 2 ) the higher patient satisfaction , the loyalty will increase ( 3 ) the higher patient satisfaction , the relational commitment will increase ( 4 ) more high loyalty , then the relational commitment will increase. Keywords : hospital , quality of service , rates , customer satisfaction , relational commitment